Modelagem sísmica por diferenças finitas em meios bidimensionais com difratores - FERNANDES, Lindemberg Lima (Universidade Federal do Pará, 2014)
The subject of this work is the seismic modeling in medium with strong discontinuities in physical properties with enphasis in diffractions events. This research intend to contribute for a better comprehension and control of seismic modeling in complex medium. According to various authors, the Amazon Basin is formed by sedimentary rocks deposited since the Ordovician to the present, reaching depth up to 5 Km. The bodies of basalt between the paleozoic sediments are arranged as basaltic layers reaching thickness of hundred meters, which add to 90,000 km3. The ocurrence of these structures is responsible for the existence of multiple reflections during the propagation of the seismic waves, which makes impossible a better imaging of horizons located bellow the basaltic layers An accoustic velocity model was used to demonstrate this geological situation. The seismograms were calculated with a program of finite-difference with a fourth order aproximation of the acoustic wave equation in space and time. The aplication of the finite-difference method for modeling the propagation of the seismic waves has improved the understanding of the wave propagation in significant heterogeneous medium and achieves a good resolution in the interpretation of seismic reflection events in areas of interest As a result of numerical experiments accomplished in a complex geological medium a significant influence due to multiple reflection observed in a high velocity layer causing an increase in a loss of energy that made the data more dificult to analise. Because of this problem I advise the integration of the data from both surface and wells, to achieve a better imaging below the basaltic layer.